Blending high performance polymers for improved stability in integrally skinned asymmetric gas separation membranes - Schulte, Leslie (Kansas State University, 2015)
Polyimide membranes have been used extensively in gas separation applications because of their attractive gas transport properties and the ease of processing these materials. Other applications of membranes, such as membrane reactors, which could compete with more traditional packed and slurry bed reactors across a wider range of environments, could benefit from improvements in the thermal and chemical stability of polymeric membranes. This work focuses on blending polyimide and polybenzimidazole polymers to improve the thermal and chemical stability of polyimide membranes while retaining the desirable characteristics of the polyimide. Blended dense films and asymmetric membranes were fabricated and characterized. Dense film properties are useful for studying intrinsic properties of the polymer blends. Transport properties of dense films were characterized from room temperature to 200°C. Properties including miscibility, density, chain packing and thermal stability were investigated. A process for fabricating flat sheet blended integrally skinned asymmetric membranes by phase inversion was developed. The transport properties of membranes were characterized from room temperature to 300°C. A critical characteristic of gas separation membranes is selectivity. Post-treatments including thermal annealing and vapor and liquid surface treatments were investigated to improve the selectivity of blended membranes. Vapor and liquid surface treatments with common, benign solvents including an alkane, an aldehyde and an alcohol resulted in improvements in selectivity.
Keywords: Polybenzimidazole; Matrimid; Polymer blending; Polymeric membrane; Gas separation membrane; Chemical Engineering (0542)